Kontribusi Konsep Sains Islam Mehdi Golshani Dalam Menyatukan Epistemologi Agama dan Sains - Rofikoh Rofikoh; Afiatul Kamilah; Alfina Wildatul Fitriyah (Yayasan Cendekia Gagayunan Indonesia, 2024)
About there is no discussion at all about the relationship between religion and science, there are some opinions that say that religion and science are in conflict, independence, dialogue and integration. Then comes the concept of integration between science and religion, namely Islamic science, which is a concept from Mehdi Gholsani in response regarding the relationship between both (religion and science). According to Mehdi Golshani, science is not just a collection theories, concepts and natural laws only. But it is also part of metaphysical reality in which divine values are stored. With In other words, science cannot be reduced to the physical realm alone, but must combined with the supernatural. So that it becomes a unit that is not can be separated between the two. The method used in this research is a document analysis method with a qualitative approach. Collection technique the data used is library research and literature study. Objective the purpose of writing this research is to understand the relationship between religion and science, knowing Mehdi Golshani's contribution to religious epistemology and science, and the concept of Islamic science according to Mehdi Golshani. This will happen discussed and is the focus of this article.